Protection of national minorities between the two world wars: A look back to some special cases - Krivokapić Boris (Međunarodni Problemi)
The work is a brief look back to some special situations between the two world wars and at the time when the so-called Versailles system was applied. This system is also well known by special solutions that were reached in the field of protection of minorities. Peace and minority agreements formed the framework for such solutions, including one-party declarations that were imposed to defeated states (except Germany) and to a number of small- and medium-sized countries. These issues were relatively comprehensively treated in the literature of that time, as well as in the publications after the Second World War. However, in parallel with this, a whole number of specific situations was resolved by adoption of special agreements that included some special situations. This is, actually, the subject of this article. If we look closely, it firstly treats special international agreements on minorities, presenting a survey of the most significant bilateral agreements on protection of minorities and other agreements, including the ones on the exchange of population. After that, the author has presented the most significant characteristics of some special situations that occurred in the period between the two world wars, concerning the status of certain territories and the position of ethnic and some other minorities as well (Dancig, Aland Islands, Upper Schlesia, Memel). Although the author notices the weak points of the considered solutions, that, after all, were of short duration, he points out that they, yet, served to achieve some results. Some of them were of great importance for that time, and they particularly contributed to resolving of some open political issues. For various reasons some of them are interesting even today, and not only as historical documents. All this suggests that the considered agreements and situations should be taken into account at our time, if nothing else, than for the fact they are a group of positive and negative experiences that as such could to some extent help find better solutions for these problems.